2020
DOI: 10.1016/j.ymgmr.2020.100647
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early-treated phenylketonuria on volumetric measures of the cerebellum

Abstract: Past murine studies of phenylketonuria (PKU) have documented significant effects on cerebellum at both the gross and cellular levels. The profile of neurocognitive and motor difficulties associated with early-treated PKU (ETPKU) is also consistent with potential cerebellar involvement. Previous neuroanatomical studies of cerebellum in patients with PKU, however, have yielded mixed results. The objective of the present study was to further examine potential differences in cerebellar morphometry between individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The small number of studies investigating GM in heterogeneous samples of patients with PKU greatly vary. On the one hand, Bodner et al 5 and Pfaendner et al 6 found smaller whole‐brain volume in patients with PKU, whereas Aldridge et al 7 and Hawks et al 8 could not find any differences. On a more regional level, smaller volumes in brain areas of the bilateral parietal and occipital lobes 9 and the motor and premotor cortex 10 were reported in patients with PKU in comparison to healthy controls.…”
Section: Introductionmentioning
confidence: 95%
“…The small number of studies investigating GM in heterogeneous samples of patients with PKU greatly vary. On the one hand, Bodner et al 5 and Pfaendner et al 6 found smaller whole‐brain volume in patients with PKU, whereas Aldridge et al 7 and Hawks et al 8 could not find any differences. On a more regional level, smaller volumes in brain areas of the bilateral parietal and occipital lobes 9 and the motor and premotor cortex 10 were reported in patients with PKU in comparison to healthy controls.…”
Section: Introductionmentioning
confidence: 95%
“…Regarding the clinical manifestations of PKU patients, usually some developmental delay, severe cognitive and psychiatric impairments can arise if PKU is left untreated [ 4 ]. Some cognitive domains such as attention [ 5 , 6 ] and psychomotor speed are usually affected even in early treated adults Aitkenhead et al, [ 49 ], as well as in other domains such as language, memory, learning, deficits in fine motor control, processing speed, and attention control [ 7 ]. Some deficits in working memory [ 5 , 8 ] and executive functions such as problem-solving, planning ability, inhibitory control, and mental flexibility have been reported as well in adults after they stopped or relaxed the diet (Pascucci et al, 2009, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bodner et al (2012) found increased putamen volumes in a sample of individuals with ETPKU as compared to individuals without PKU. Christ et al (2016) and Aldridge et al (2020) reported ETPKU-related decreases in cortical parietal and cerebellar gray matter volumes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These white matter abnormalities have a primary focus near the trigone of the lateral ventricles and may extend anteriorly with increased severity. There is also growing evidence that cortical, subcortical, and cerebellar gray matter structures may be affected as well (Aldridge et al, 2020; Bodner et al, 2012; Christ et al, 2016).…”
Section: Motor Learningmentioning
confidence: 99%